Normal Subjects Consuming Physiological Levels of 18:3(n-3) and 20:5(n-3) from Flaxseed or Fish Oils Have Characteristic Differences in Plasma Lipid and Lipoprotein Fatty Acid Levels - Layne, Kim S.; Goh, Yeow K.; Jumpsen, Jacqueline A.; Ryan, Edmond A.; Chow, Peter; Clandinin, Michael T. (The Journal of nutrition, 1996)
The study assessed the effect of low doses of fatty acids from fish or flaxseed oil on plasma lipid concentrations in normal humans consuming diets with either high (0.87, n = 11) or low (0.48, n = 15) dietary polyunsaturated/saturated fatty acid (P/S) ratios. The dose of (n-3) fatty acids reflected an (n-3) intake that could easily be attained by selection of foods in a normal diet. The individuals were initially supplemented with olive oil [35 mg 18:1/(kg body weight · d)], and then were randomly assigned to either flaxseed or fish oil [35 mg 18:3(n-3) or 35 mg 20:5(n-3) + 22:6(n-3)/(kg body weight · d), respectively] treatments. Participants consumed each oil supplement for 3 mo. Blood samples were drawn for analysis at the end of each 3-mo period. Plasma triacylglycerol, total, LDL and HDL cholesterol concentrations, and lipoprotein fatty acid concentrations are shown. Fish oil reduced plasma triacylglycerol and increased lipoprotein levels of 20:5(n-3) and 22:6(n-3). The flaxseed oil did not alter plasma triacylglycerol level and produced small changes in 20:5(n-3) and 22:6(n-3) concentrations. Total, LDL and HDL cholesterol levels were not affected by either (n-3) fatty acid. Significant differences in plasma triacylglycerol concentrations and total and LDL cholesterol levels were found between the two dietary P/S groups after all oil treatment periods. Levels of 18:3(n-3), 20:4(n-6), 20:5(n-3), and 22:6(n-3) in LDL were also different in high vs. low dietary P/S groups for all oil treatments and in the VLDL for the olive oil and fish oil supplementation. This study indicates that low intake of purified fish oil induces changes in plasma triacylglycerol, 20:5(n-3) levels in VLDL, LDL, and HDL, and 22:6(n-3) levels in LDL and HDL that are apparent after 3 mo and which might influence atherogenicity of lipoprotein particles in normal free-living individuals.